Producción de corto animado bajo técnicas digitales sobre el impacto ambiental causado por el consumo irresponsable de recursos naturales - Marchán Ordóñez, Manuel Emilio (2015)
Over the years the number of people living in this planet has increased and with them the amount of resources used to satisfy the lifestyle of a population that consumes more than their needs dictate. Gradually natural resources are disappearing, despite the efforts by the community to inform about the risks that will bring in the future, a large part of the population is unaware of the problem and refuses to change to improve the situation. For this reason, is really important to teach children and adolescents in a correct way, especially because they are more susceptible and more adaptable beings. In order to develop an attractive product for children, it is necessary to make a previous investigation about their preferences. The result of this process was the creation of an animated short film, in which you can appreciate the creation of life that is given by nature and the contrast with the human being who is in charge of destroying it for their own profit, regardless of the consequences that this may bring.